Beyond handshakes and agreements: The real work behind scaling conservation agriculture in Malawi - Kudzanai Chimhanda (CIMMYT, 2025)
Forged in the fields of Malawi, CIMMYT and Total LandCare’s partnership is proving that climate-smart farming rooted in local realities can transform livelihoods, one resilient harvest at a time.